Development of a Gastropod Diversity Booklet from Lagundri Beach, South Nias, as a Biology Learning Resource for Senior High School on the Topic of Biodiversity - Diana Buulolo; Masdiana Sinambela; Hasruddin (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2026)
This study aimed to identify the diversity of gastropods at Lagundri Beach, South Nias, and to develop and evaluate the feasibility, practicality, and effectiveness of a booklet as a biology learning resource for senior high school students on the topic of biodiversity. This research employed a Research and Development (R&D) approach using the 4D model (define, design, develop, disseminate). The research subjects consisted of five validators, two teachers, and 31 students. Data were analyzed quantitatively and qualitatively through validity, practicality, and effectiveness tests, with effectiveness assessed using normality, homogeneity, t-test, and N-gain analyses. The results showed that the gastropod diversity index was 3.31, which falls into the high category. The developed booklet was classified as highly feasible (average >88%), highly practical (≥91%), and moderately effective, with an N-gain value of 63.13%. The t-test indicated a significant difference between the experimental and control classes (t = 4.80; p < 0.05). Therefore, this booklet based on local potential is suitable for use as a supplementary learning resource to improve students’ conceptual understanding and biodiversity literacy.